Práticas pedagógicas no âmbito do ensino médio : abordagens de temáticas ambientais em um colégio de tempo integral da rede estadual de ensino da Bahia - Jesus, Lucivania Mota de (2025)
The research entitled Pedagogical Practices in the scope of High School: approaches to environmental themes in a Full-Time School of the State Education Network of Bahia, linked to the Postgraduate Program in the National Network for Teaching Environmental Sciences (PROFCIAMB/UEFS) aimed to understand how the pedagogical practices of teachers who work in High School, problematize themes of Environmental Education, in a Full-Time College, of the State Education Network of Bahia. The theoretical basis of the research was in dialogue with authors such as Freire (1996; 2022; 2023) Saviani (2016; 2021) and hooks (2024), collaborating with the discussions that permeate the conception of education, in order to generate elements of study and reflection on pedagogical practices, anchored in Veiga (2008), Caldeira and Zaidan (2010) and Franco (2016; 2020; 2021). We support the reflections on Critical Environmental Education, based on Reigota (2009); Layrargues and Lima (2014), Loureiro (2019; 2022) and Layrargues (2020; 2022). We analyzed the normative curricular documents that guide Basic Education, based on the National Common Curricular Base (BNCC, 2018), National Curricular Guidelines for High School (DCNEM, 2018) and the Bahia Reference Curricular Document (DCRB, 2022) - High School stage, as well as the guiding documents of the Bahia State Education Network. Based on the research object, a qualitative approach was chosen, inspired by the contributions of collaborative research. The research techniques chosen were document analysis and Conversation Circles, with the research locus being a Full-Time College of the State Education Network of Bahia. The research collaborators were seven teachers who teach curricular components of the National Common Curricular Base and the Training Itineraries. The analysis and reflection of the Conversation Circles revealed that the teachers participating in the research present conceptions of Environmental Education that align with the critical perspective, so that they recognize the relevance of approaching Environmental Education, based on the problematization of local reality, for the critical formation of students. However, teachers point out challenges of the New Secondary Education (NEM), such as work overload and curricular fragmentation as obstacles to the development of pedagogical practices. The educational product resulting from the research consists of a Notebook with didacticpedagogical guidelines that aims to support teaching work based on the problematization of Environmental Education themes, from a critical perspective. The elaboration took place collaboratively with the professors participating in the research and is based on the theoretical framework that underpins this research.